(untitled) (Bangladesh Journal of Medical Microbiology, 2017)
Bacterial infection is an important complication among children with cancer, who are under chemotherapy. Bacterimea may occur during chemotherapy, which is an invasive procedure and also due to reduced number of neutrophil count. The study was conducted in a tertiary level hospital, Bangabandhu Sheikh Mujib Medical University in Bangladesh from March to September 2010. The aim of this study was isolation and identification of bacteria from blood culture among children with febrile neutropenia who were under chemotherapy. Blood samples were collected from 30 febrile neutropenic children and culture was done by traditional culture method using Trypticase soy broth for primary culture. Out of 30 blood samples, culture were positive in 6(20%) and were negative in 24(80%) samples. Two third of the culture positive patients had absolute neutrophil count (ANC) less than 100 cells/cmm. The isolated organisms were Pseudomonas spp (33.3%) Staphylococcus aureus (33.3%), Esch. coli (16.7%) and Acinetobacter spp (16.7%). Amikacin, imipenem and meropenem were the most effective antibiotics having 100% sensitivity. Blood culture is essential to evaluate the febrile neutropenic children who were under chemotherapy. Bangladesh J Med Microbiol 2015; 9 (1): 9-12